THU0454 Increased fdg uptake of the muscles in polymyalgia rheumatica (PMR). (12th June 2018) - Cimmino, M.A.; Vecchiola, N.; Bauckneht, M.; Camellino, D.; Morbelli, S.; Paolino, S.; Cutolo, M.; Sambuceti, G.
Abstract : Background: PMR is an inflammatory disease affecting the shoulder and pelvic girdles of elderly patients. Its causes, development mechanisms and anatomical targets of inflammatory damage are still elusive. Synovitis, vasculitis, and bursitis have all been demonstrated in PMR but data on muscles are scanty. Objectives: Our study evaluated muscular uptake at FDG-PET/CT in patients with PMR. Methods: Fifty patients with PMR diagnosed according to Bird et al criteria and 50 age- and sex-matched control patients without inflammatory disorders, who underwent FDG-PET/CT to rule out malignancy, were studied. Standard FDG-PET/CT examination was performed and its results were evaluated by both qualitative scoring, on a 5-grade scale from 0 (no uptake) to 4 (clearly higher than liver uptake), and analysis of the standardised uptake value (SUV max and mean) in a ROI placed on the deltoid, byceps, gluteus and quadriceps muscles. A ROI of the joints and bursae was also designed and the SUV calculated. The muscle ROIs were positioned distant from the corresponding joints to avoid interference from possible articular or periarticular uptake. Demographic, clinical and laboratory data were collected. Results: PMR patients showed an uptake higher than that of controls in the deltoid (p=0.0004), gluteus (p=0.015), and quadriceps (p=0.009), but not in the biceps (p=0.06) muscles. The semiquantitative SUV evaluation was consistent for the deltoid (SUV mean, p=0.047) and gluteus (SUV mean, p=0.01; SUV max, p=0.006) muscles. There was no correlation between muscle uptake and that of the adjoining joint. Similarly, no correlation was found between muscle uptake and demographic, clinical and laboratory (CRP, ESR) findings. Conclusions: PMR show muscular inflammation at FDG-PET/CT, which does not derive from the nearby joints or periarticular tissues. A clearly defined myositis is not probable, because creatine kinase concentrations are normal in PMR. However, muscle inflammation may contribute to the global inflammatory burden and symptoms of patients with PMR. Disclosure of Interest: None declared